(untitled) (Comparatismi, 2020)
Alla luce dei recenti studi psicologici sulla relazione tra narrazione e sviluppo della personalità, vengono qui tracciati alcuni dei punti chiave emersi in questo campo: il condizionamento reciproco che esiste tra le narrazioni personali e quelle predominanti, vigenti, con cui interagiamo, i passaggi che costituiscono la costruzione di un’identità narrativa ed infine le discrepanze che si avvertono tra la propria esistenza e ciò che si dovrebbe o potrebbe essere. Tale panoramica mantiene il fuoco sull’influsso che tali narrazioni operano nei confronti della personalità e della sua evoluzione. __ In the light of recent psychological studies on the relationship between narratives and personality development, we outline some of the key points that have ultimately emerged more clearly in this field. The main aspects are related to the mutual conditioning that exists between personal and master narratives, the construction of a narrative identity based on the socio-cultural context, the steps that involve the narrative construction of personality and the discrepancies that are felt between one’s own existence and what it should or could be. This overview keeps the focus on the influence that these narratives have on the personality and vice versa, and how a coherence between them is strictly necessary.